Recurrent aphthous stomatitis (RAS): a preliminary within-subject study of quality of life, oral health impacts and personality profiles - AL-Omiri, Mahmoud K.; Karasneh, Jumana; Alhijawi, Mohannad M.; Zwiri, Abdalwhab M. A.; Scully, Crispian; Lynch, Edward (Journal of oral pathology & medicine, 2015)
Background RAS may affect quality of life and impacts oral health and daily activities; consequently, psychological factors, dental needs and patients’ perceptions. Professionals should understand this relation to adequately manage oral ulcers. This study aimed at investigating the relationship between oral health impacts, oral health‐related quality of life and psychological profiles in patients with recurrent aphthous stomatitis (RAS). Methods Fifty‐three patients (30 men and 23 women, mean age: 31.1 ± 10.1 years) with RAS participated in this study. During ulcer episodes, participants completed Hospital Anxiety and Depression Scale (HAD), Neuroticism‐Extraversion‐Openness Five Factor Inventory (NEO‐FFI), Oral Health Impact Profile (OHIP‐14) and United Kingdom Oral Health‐Related Quality of Life measure (OHQoL‐UK) proformas. Patients completed OHIP‐14 and OHQoL‐UK again when they were ulcer‐free. The statistically significance levels were set at P ≤ 0.05. Results During ulcer episodes, patients reported worse oral health impacts and an inferior quality of life in comparison with ulcer‐free times (P < 0.0001). Higher OHIP scores were significantly associated with higher HAD depression (P = 0.036) and anxiety (P = 0.012) scores. NEO‐FFI scores had no significant relations with OHIP and OHQoL‐UK scores (P > 0.05). During ulcer‐free periods, no relationships were detected between OHIP, OHQoL‐UK, HAD and NEO‐FFI scores (P > 0.05), except between OHQoL‐UK and conscientiousness scores (P = 0.05). Conclusions RAS increased the negative oral health impacts on patients and consequently lowered their quality of life. Stressful situations and conditions (including anxiety and depression), rather than inherent personality profiles and stable psychological traits, were related to oral health impacts and quality of life in patients with RAS.